PENGARUH KONDISI FUNDAMENTAL, INFLASI, DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA TERHADAP HARGA SAHAM (Study Kasus pada Perusahaan Real Estate dan Property yang terdaftar di Bursa Efek Indonesia tahun 2010-2013) - Dewi Kusuma Wardani; Devita Fajar Tri Andarini (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
This research is motivated by the results of researches differences which have been done by other researchers. Moreover, it is also because construction companies in the sector of Real Estate and Property which develops a lots. The developing influences the stock prices in the sector of Real Estate and Property in Indonesia. This study aimed to examine the effect of the fundamental conditions, inflation, and SBI interest rates on the stock prices. This research is done in Pojok Bursa Efek Indonesia. the fundamental factors which are used in this research is Current Ratio, Return on Asset, Debt Equity Ratio, and Total Asset Turn Over. The data which are used are the secondary data which are taken from IDX with 180 populations, and 132 data are treated. The sampling method in this research is purposive sampling. The data technique analysis in this research uses multiple linear regression techniques. The regression test results show that the influence of fundamentals, inflation, and SBI interest rates partially positive effect on stock prices. The third influence of independent variable on the dependent variable is just 10.5%. It is necessary for the addition of variables in future researches. Keyword: fundamental conditions, inflation, SBI interest rates, and stock prices